Multidisciplinary Approach to Optimize the Health of Children with Medical Complexity Undergoing Orthopaedic Surgery: Quality, Safety and Value - Mason, Sheila L.; Sebesta, Megyn R.; Snow, Sybil; Frino, John; Gyr, Bettina; Nageswaran, Savithri; Jeanna R. Auriemma; Haberman, Cara (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Background: The study objective was to determine whether a multidisciplinary, comprehensive preoperative assessment and co-management structure improved the perioperative course in children with medical complexity (CMC) undergoing orthopaedic surgery. Data was collected from three phases, standard of care, partial optimization review process, and full optimization review process. By the last phase, patients were seen for a pre-surgical optimization review by the pediatric nurse practitioner (PNP), followed by coordination with the pediatric complex care team and the patient’s sub-specialty providers. Gaps in the patient’s care that would limit clearance for surgery, as identified during the optimization review, were addressed and then comprehensive care plans were created preoperatively. Patients were treated postoperatively with a co-management framework between the pediatric medical management teams and orthopaedic services. Results: There were 90 children who met inclusion criteria for retrospective chart review. Cerebral palsy was the leading primary diagnosis (n=62). Posterior spinal fusion (n=37) and hip containment (n=37) procedures were the most frequent procedures. Twenty nine children underwent formal review with a statistically significant increase in review completion between phase 2 and phase 3 (p=0.001). A statistically significant number of patients who underwent review were found to have gaps in care (n=21; p= <0.00001). Additionally, patients reviewed were 1.92 times more likely to receive anticipatory guidance than patients who did not have review (p= < 0.00001). Length of stay for children undergoing review was relatively stable at 3.18 days compared to 3.51 days for those who did not undergo review. There was a decreased time to resumption of enteral feeds by 51.3% (p=0.007743). Most notably, there was elimination of rapid responses and transfers to higher level of care in patients that underwent health optimization. Among phases there was a 42.8% reduction in post-operative complications. This reduction however did not correlate directly with those who received health optimization review versus those that did not (p=0.954068). Conclusion: A preoperative optimization program and co-management model improves the CMC’s surgical readiness and postoperative outcomes.